Electrochemical Sensor for Hydrogen Leakage Detection at Room Temperature - Gimi Aurelian Rîmbu; Lucian Pîslaru-Dănescu; George-Claudiu Zărnescu; Carmen Alina Ștefănescu; Mihai Iordoc; Aristofan Alexandru Teișanu; Gabriela Telipan (Sensors)
The use of hydrogen as fuel presents many safety challenges due to its flammability and explosive nature, combined with its lack of color, taste, and odor. The purpose of this paper is to present an electrochemical sensor that can achieve rapid and accurate detection of hydrogen leakage. This paper presents both the component elements of the sensor, like sensing material, sensing element, and signal conditioning, as well as the electronic protection and signaling module of the critical concentrations of H2. The sensing material consists of a catalyst type Vulcan XC72 40% Pt, from FuelCellStore, (Bryan, TX, USA). The sensing element is based on a membrane electrode assembly (MEA) system that includes a cathode electrode, an ion-conducting membrane type Nafion 117, from FuelCellStore, (Bryan, TX, USA). and an anode electrode mounted in a coin cell type CR2016, from Xiamen Tob New Energy Technology Co., Ltd, (Xiamen City, Fujian Province, China). The electronic block for electrical signal conditioning, which is delivered by the sensing element, uses an INA111, from Burr-Brown by Texas Instruments Corporation, (Dallas, TX, USA). instrumentation operational amplifier. The main characteristics of the electrochemical sensor for hydrogen leakage detection are operation at room temperature so it does not require a heater, maximum amperometric response time of 1 s, fast recovery time of maximum 1 s, and extended range of hydrogen concentrations detection in a range of up to 20%.